Analyzing Articles Reviews Using Neural Network (Al-Mansour Journal, 2023)
Artificial Intelligence (AI) can increase the efficiency of industrial production compared to human effort. There is a continual increase in artificial intelligence (AI), which is driven by the fact that this technology is increasing with "Industry 4.0" and the costs of it are decreasing. This paper deals with applying Natural Network to analyze data of (9) article reviews from January till June 2022 and focuses on the latest reviews for "industrial 4.0" for business & accounts .The objectives of this work is to understand the information contained in nine article reviews (723 study). Article reviews many conclusions. In this article, our model has the moderate ability to predict "industrial 4.0" articles in advance under the simulated situation with real-world data. This brief review estalish a model that can be used to analyze nonlinear behaviour in small datasets and identify causal relationships in this paper.
Keywords: Artificial Natural Network; article reviews; industrial 4.0; business and accounts